Ethical-functional compliance in federal educational institutions: An essay from the perspective of technical administrative in education (Research, Society and Development, 2021)
This essay was designed to present to technical-administrative servers in education (TAES) the main areas concerned with their conduct and ethical-functional training. These areas, sometimes, can be unduly triggered or even unknown by a large part of the academic community, such as: Ethics Commission, Internal Commission for Supervision of the Career Plan of Technical-Administrative Positions in Education, Ombudsman and Disciplinary Activity. Thus, the work seeks to present the main competences and influences that they can exert on the TAES. This is a theoretical essay, with a qualitative approach, which is based on the authors' professional experience. It is expected to contribute with an adequate understanding of the functions of each of the areas, so that there is no appropriation or overlapping of competences.